Match-play running demands of professional female Rugby Sevens: Comparison of ball-in-play, worst-case scenarios and game phases in Super Sevens 2023 - Bicudo, F. O.; Figueiredo, L. S.; Azevedo, A. P. d. S.; Pedrosa, G. F.; Castro, H. d. O. (International Journal of Sports Science & Coaching, 2025)
A gray area remains about the intensity of efforts performed in Sevens competitions, especially during the worst-case scenarios (WCS - longest effort during a match). For this reason, the analysis of demands during the ball-in-play (BIP) is increasing in team sports like Rugby Sevens. Through this method, we can also identify the WCS and the demands of distinct phases of play (attack, defense, and transition). Thus, this study aimed to (i) investigate and compare the BIP and WCS external load (EL) demands (distance per minute, sprint distance per minute, and accelerations per minute) during matches; and (ii) compare the BIP running demands across different game phases (attack, defense, and transition). Twenty-one female professional Rugby Sevens players participated, with their running demands analyzed during every BIP phase in all 20 matches of the Super Sevens 2023 using individual GPS tracking. The results indicated no significant differences in any EL variables between WCS and BIP averages. Furthermore, there were no differences in EL experienced by athletes during different phases and actions. In summary, our findings suggest that both the WCS and the BIP methods result in similar EL values across matches. Additionally, the EL remains consistent across different game periods (first half vs. second half) and actions (defense, attack, and transition). These results offer practical guidance for coaches when planning training sessions for female Rugby Sevens athletes, suggesting that preparation focused on WCS may effectively prepare athletes for the entire game.